Cytokine Expression in Peripheral Blood Mononuclear Cell Cultures Obtained from Cattle with Different Stages of Natural Mycobacterium bovis Infection - Lugo-Arriaga, María Teresa; Jaramillo-Meza, Laura; Manzo-Sandoval, Anabelle; Díaz-Otero, Fernando (Journal of Veterinary Healthcare, 2021)
In bovine tuberculosis (bTB), cellular, humoral, or both types of immune responses have been observed. The purpose of this study was to examine the immune status of tuberculous cows based on the differential cytokine gene expression associated with Th1 (IFN-γ, IL-2), or Th2 (IL-4, IL-10) responses. Twenty-three (23) cows belonging to a dairy herd located in a rural region of the State of Hidalgo, México, were selected for the study. Single Intradermal Comparative Cervical Tuberculin (SICCT) Test, Interferon-Gamma (IFN-γ) Release Assay (BOVIGAM), and Enzyme-Linked Immunosorbent Assay (ELISA) were used for detection of cattle infected by M. bovis. Thirteen cows were positive to all the tests (Group 1); ten cows were positive only to ELISA (Group 2), and the remaining Group (Group 3, control) included cows negative to all the tests. Peripheral blood mononuclear cells (PBMC) from animals were in vitro stimulated by bovin purified protein derivative (PPD), avian PPD, and Concanavalin A (Con A) mitogen for 72h. Changes in the levels of expression of mRNA of the respective cytokines was measured by Reverse Transcription-Polymerase Chain Reaction (RT-PCR) using β-actin gene as internal control. In group 1, PPD bovis and Con A-stimulated cells exhibited high production of IFN-γ, IL-2 and IL-4, but not IL-10. In contrast, PPD avium-stimulated cells displayed a low production of cytokine transcripts. In group 2, cells showed a significant production of IL-10 in response to bovine PPD (P< 0.001). In the control group, a high production of IFN-γ and IL-2 was observed only in Con A-stimulated cells. Post-mortem examinations in animals of group 1 showed slight and medium lesions in lymph nodes, whereas in group 2, the lesions were more extensive. Results indicate differences on gene expression levels of cytokines considered to determine balance in Th1/Th2 response among the evaluated groups. In addition, high levels of antibodies against M. bovis and high IL-10 expression in PBMC together are indicators of progressive bTB when both tuberculin test and IFN-γ assay are negative in tuberculous anergic cattle. Inclusion of serology and IL-10 cytokine expression in in the diagnosis checklist improves detection of infected cattle to help control bovine tuberculosis.
Keywords: Tuberculosis